Role of pH in the Aqueous Phase Reactivity of Zerovalent Iron Nanoparticles with Acid Orange 7, a Model Molecule of Azo Dyes. (11th June 2017) - Freyria, F. S.; Esposito, S.; Armandi, M.; Deorsola, F.; Garrone, E.; Bonelli, B.
Abstract : The effect of both pH and surface oxidation of nanoparticles is studied on the interaction between a commercial slurry of Nanoscale Zerovalent Iron (NZVI) and the azo dye Acid Orange 7 (AO7). NZVI is a reducing agent used for the degradation of several pollutants, including azo dyes: during pollutant degradation, it undergoes progressive oxidation and dissolution. Though it is generally acknowledged that NZVI consists of core-shell nanoparticles, where the core of metallic iron is covered by F e x O y shell, it still remains a poorly defined system. In this work, the solid fraction recovered by filtration and drying was characterized by means of XRD diffraction with Rietveld refinement, N2 isotherms at 77 K, FE-SEM and TEM observation, EDX analysis, and IR spectroscopy. Powders were obtained from both the parent slurry and the same slurry pretreated with HCl in order to remove F e x O y shell, finally reactivating the nanoparticles. The aforementioned physicochemical characterization allowed figuring out some correlations between the properties of the studied nanomaterial and the processes occurring when it is in contact with AO7 in aqueous phase. The type of interaction occurring within the NZVI/AO7 system (adsorption and type of redox reactions) strongly depends not only on the pH of the starting solution, but also on the surface oxidation of the nanoparticles.